Limited Mitochondrial Activity Coupled With Strong Expression of CD34, CD90 and EPCR Determines the Functional Fitness of ex vivo Expanded Human Hematopoietic Stem Cells - Papa, Luena; Djedaini, Mansour; Martin, Tiphaine C.; Zangui, Mahtab; Beaumont, Kristin G.; Sebra, Robert; Parsons, Ramon; Schaniel, Christoph; Hoffman, Ronald (Frontiers in Cell and Developmental Biology, 2020)
Ex vivo expansion strategies of human hematopoietic stem cell (HSC) grafts with suboptimal stem cell dose have emerged as promising strategies for improving outcomes of HSC transplantation in patients with hematological malignancies. While exposure of HSCs to ex vivo cultures expands the number of phenotypically identifiable HSCs, it frequently alters the transcriptomic and metabolic profiles, therefore, compromising their long-term (LT) hematopoietic reconstitution capacity. Within the heterogeneous pool of expanded HSCs, the precise phenotypic, transcriptomic and metabolic profile and thus, the identity of HSCs that confer LT repopulation potential remains poorly described. Utilizing valproic acid (VPA) in ex vivo cultures of umbilical cord blood (UCB)-CD34+ cells, we demonstrate that expanded HSCs phenotypically marked by expression of the stem cell markers CD34, CD90 and EPCR (CD201) are highly enriched for LT-HSCs. Furthermore, we report that low mitochondrial membrane potential, and, hence, mitochondrial activity distinguishes LT-HSCs within the expanded pool of phenotypically defined HSCs. Remarkably, such reduced mitochondrial activity is restricted to cells with the highest expression levels of CD34, CD90 and EPCR phenotypic markers. Together, our findings reveal that high expression of CD34, CD90 and EPCR in conjunction with low mitochondrial activity is critical for identification of functional LT-HSCs generated within ex vivo expansion cultures.